Pengaruh Personality Traits dan Dukungan Universitas Mengenai Green Entrepreneurial Terhadap Minat Mahasiswa pada Green Entrepreneurial dengan Nilai Lingkungan Sebagai Variabel Moderasi - Fahira, Diva; Maslichah, Maslichah; Rudiningtyas, Dyah Arini (Universitas Islam Malang, 2024)
This research aims to determine the influence of personality traits and University support regarding green entrepreneurship on students' interest in green entrepreneurship by considering the moderating variable environmental values. Using a quantitative approach, the sample processed was 100 respondents from FEB UNISMA students Class of 2020. The results of this research are: 1) Personality traits have a significant negative effect on students' interest in green entrepreneurship 2) University support regarding green entrepreneurship has a significant positive effect on students' interest in green entrepreneurial 3) Environmental values have a significant positive effect on students' interest in green entrepreneurship 4) Environmental values moderate the influence of personality traits on students' interest in green entrepreneurship 5) Environmental values moderate the influence of University support regarding green entrepreneurship on students' interest in green entrepreneurship.Keywords: Personality traits, university support, environmental values, green entrepreneurial